2020
DOI: 10.3390/met10101388
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surfactant Structure on the Development of a Sustainable and Effective Cutting Fluid for Machining Titanium Alloys

Abstract: In cutting operations of titanium alloys, most of the problems are related to the high consumption of cutting tools due to excessive wear. An improvement of metalworking fluid (MWF) technology would increase the productivity, sustainability, and quality of machining processes by lubricating and cooling. In this research article, the authors varied the surfactant’s charge, the hydrocarbon chain length, and the ethoxylation degree. Surfactants were dispersed at 1.2 mM in water and trimethylolpropane oleate to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…RSM method suggested that both the surface roughness and tool wear fit linear models with relatively high R 2 of 92% and 99%, respectively. The linear models representing the two responses can be described as functions of the cutting fluid concentration (c), cutting speed (v), feed rate (f), and cutting tool type, and are expressed as in equation [2]. The coefficients' values for the surface roughness and tool wear (for different tool types) are shown in Tables 5 and 6, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSM method suggested that both the surface roughness and tool wear fit linear models with relatively high R 2 of 92% and 99%, respectively. The linear models representing the two responses can be described as functions of the cutting fluid concentration (c), cutting speed (v), feed rate (f), and cutting tool type, and are expressed as in equation [2]. The coefficients' values for the surface roughness and tool wear (for different tool types) are shown in Tables 5 and 6, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the same properties that give the alloys superior qualities also make them notoriously difficult to cut, owing to their low thermal conductivities, high dynamic shear strength and high hardness (e.g. up to 360 HV for Ti-6Al-4V), and high chemical reactivity at elevated temperatures [1,2]. Low thermal conductivity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The authors [15] found that the use of flux based on this powder composition contributes to forming a thicker and denser layer of intermetallides due to high temperature. The peculiarity of works [16] is that this composition of titanium-aluminium powders is limited by their existence's physical and chemical conditions. In many cases, increased requirements are placed on the performance characteristics of parts with design elements that are made based on titanium alloys [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, it provides cost savings in machining. The cutting liquid or coolant's or MWF's main objective is to expel the heat produced by friction between the workpiece and the cutting tool, which ultimately decreases the upsurge in temperature of the cutting tool [8]. Besides, cutting fluid also aids in the flushing of the produced chips during the machining process.…”
Section: Introductionmentioning
confidence: 99%